1996
DOI: 10.1007/bf01486737
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced lung injury in vivo: Expression of transforming growth factor?Beta precedes fibrosis

Abstract: Cytokine release from irradiated cells has been postulated to start soon after irradiation preceding detectable clinical and pathological manifestation of lung injury. The expression of transforming growth factor beta (TGF beta), a fibrogenic and radiation-inducible cytokine, was studied from 1-16 weeks after the 15 and 30 Gray (Gy) of thoracic irradiation to rats. Thoracic irradiation caused an increase in TGF beta protein in bronchoalveolar lavage (BAL) fluid peaking at 3-6 weeks as compared to sham-irradiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 24 publications
5
31
0
Order By: Relevance
“…Pulmonary expression of TGF-␤ 1 , a major regulator of extracellular matrix components, including collagens, is upregulated in several rodent models of pulmonary fibrosis, including a rat model of AM-induced pulmonary fibrosis (Yi et al, 1996;Iyer et al, 1999;Chung et al, 2001). In the present study, significant up-regulation of TGF-␤ 1 mRNA expression was observed 7 and 21 days after AM treatment, whereas hydroxyproline content was not elevated until 21 days, supporting a central role for this cytokine in the tissue Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary expression of TGF-␤ 1 , a major regulator of extracellular matrix components, including collagens, is upregulated in several rodent models of pulmonary fibrosis, including a rat model of AM-induced pulmonary fibrosis (Yi et al, 1996;Iyer et al, 1999;Chung et al, 2001). In the present study, significant up-regulation of TGF-␤ 1 mRNA expression was observed 7 and 21 days after AM treatment, whereas hydroxyproline content was not elevated until 21 days, supporting a central role for this cytokine in the tissue Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that radiation causes induction of TGF-␤ (3,24,40), although the mechanisms of radiationinduced TGF-␤ activation are poorly understood. One suggested mechanism is oxidation dependent activation through redox-related mechanisms (4).…”
Section: L883 Radiation Induces Lactate Production In Lung Fibroblastsmentioning
confidence: 99%
“…TGF-␤ has been implicated in the development of radiation-induced fibrosis in several organs including the skin, lung, and liver (24,30,40) and TGF-␤ levels in the lung increase in the weeks following thoracic radiation (9,31,40). However, the mechanism of TGF-␤ activation in radiation-induced fibrosis remains poorly understood.…”
mentioning
confidence: 99%
“…It has been reported that granulocyte-macrophage colony-stimulating factor and transforming growth factor ␤ inhibit AM-mediated suppression of lymphocyte proliferation [20]. These cytokines are increased in BALF during lung inflammation [25,26]. Mucin as a component of mucus is also increased in BALF during lung inflammation [27,28].…”
Section: Discussionmentioning
confidence: 99%